Message from the Chief Editor: service excellence attitudes amidst COVID-19 pandemic / Boo Ho Voon - Boo, Ho Voon
The deadly coronavirus disease which started in the year 2019 (COVID-19,as named by the World Health Organization) is a grave threat to mankind. This COVID-19 pandemic has caused the loss of many lives worldwide.Henceforth, this omni-present and dangerous virus need to be curbed soonest possible and the entire world needs to do its best with love andcare to contain the pandemic. As being said, all stakeholders at different levels need to join hands and work together consistently and continuously to achieve service excellence for sustainability.